2017
DOI: 10.1111/1755-5922.12277
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane protection against the development of doxorubicin‐induced chronic heart failure is associated with Nrf2 Upregulation

Abstract: We arrived at the conclusion that DOX-induced CHF can be prevented by SFN through the upregulation of Nrf2 expression and transcriptional function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 40 publications
5
34
0
Order By: Relevance
“…The attention given to this natural compound is constantly growing due to its multiple pharmacological activities. It has been demonstrated that sulforaphane is effective in brain and neuronal injury with neuroprotective effects [1,2]; in renal [3,4] and liver damage models [5]; in hyperglycemia and β-cell damage [6]; and in damage to the heart, cardiac cells, and other tissues [7]. Sulforaphane is mostly characterized by its potent anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…The attention given to this natural compound is constantly growing due to its multiple pharmacological activities. It has been demonstrated that sulforaphane is effective in brain and neuronal injury with neuroprotective effects [1,2]; in renal [3,4] and liver damage models [5]; in hyperglycemia and β-cell damage [6]; and in damage to the heart, cardiac cells, and other tissues [7]. Sulforaphane is mostly characterized by its potent anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the accumulative doses of DOX was 15 mg/kg body weight. [13][14][15] As for the judgment of CHF model, hemodynamic indices were comprehensively assessed by a RM6240 multi-channel physiological signal acquisition system (Chengdu Instrument Factory, Sichuan, China) as our previous studies. [16][17][18][19] When the values of +dp/dt max were reduced to 50% of the control group, CHF model was successfully prepared.…”
Section: Animal Handlingmentioning
confidence: 99%
“…Suppression of NLRP3 inflammasome alleviating acute gouty inflammation [147] Modification of Histone H3, unpacking of chromatin, to prime defence [104] Nrf2-Inducers Counteract Neurodegeneration in Friedreich's Ataxia [148] Modulation of oxidative stress and inflammation in rats with toxic hepatitis [149] Modulation of oxidative damage in lead exposed rat hippocampus [150] Prevention of dexamethasone-induced myotube atrophy via Akt/Foxo1 [151] Induction of p53 deficient SW480 cell apoptosis by ROS MAPK signalling [152] Role of microRNAs in the chemo preventive activity of SFN [153] Up regulation of Nrf2 protection in doxorubicin-induced chronic heart failure [154] Increased Nrf2 expression protects alveolar epithelial cells against oxidative injury [155] Novel phosphonate analogs of SFN with in vitro and in vivo anticancer activity [156] Inhibition of PDGF-induced vascular SMC proliferation by targeting mTOR/p70S6kinase signalling independently of Nrf2 activation [157] Gastrointestinal protection against H. pylori and NSAID-Induced Oxidative Stress [158] Protection from cerebral ischemic/reperfusion injury via inhibition of NLRP3 inflammasome activation in rats [159] Protection against sodium valproate-induced acute liver injury [160] Enhanced SFN cardioprotection against oxidative stress by 17β-Estradiol [160] Photoprotective Effects of SFN and Hispidulin [106] Differential modulation of mitochondrial biogenesis/dynamics in normal and tumour cells [161] Nrf2 targeting by SFN: A potential therapy for cancer treatment [162,163] Improvement of neuronal mitochondrial function in brain tissue [164] Protection of pancreatic Acinar cell injury by modulating Nrf2-mediated oxidative stress and the NLRP3 inflammatory pathway [165] Improvement in chemotherapy efficacy targeting cancer stem cell-like properties [166] Protection against rotenone-induced neurotoxicity via mTOR, Nrf2, and autophagy [167] Chemoprevention of oxidative stress-associated with oral carcinogenesis [168] Amelioration of bladder dysfunction via activation of Nrf2-ARE Pathway [169] Broccoli sprout homogenate treatment for Sickle Cell Disease …”
Section: The Diverse Areas Of Application Of Sulphoraphane (Sfn) In Bmentioning
confidence: 99%